Contemporary tourist experience : concepts and consequences - Sharpley, Richard, 1956-; Stone, Philip R. (Routledge advances in tourism, 2012)
This significant and timely volume aims to provide a focused analysis into tourist experiences that reflect their ever-increasing diversity and complexity, and their significance and meaning to tourists themselves. Written by leading international scholars, it offers new insight into emergent behaviours, motivations and sought meanings on the part of tourists based on five contemporary themes determined by current research activity in tourism experience:conceptualization of tourist experience; dark tourism experiences; the relationship between motivation and the contemporary tourist ...